2020
DOI: 10.3390/fib8080049
|View full text |Cite
|
Sign up to set email alerts
|

A New Fabric Reinforced Geopolymer Mortar (FRGM) with Mechanical and Energy Benefits

Abstract: A large part of the European building Heritage is dated back over centuries. Consequently, its structural and thermal performances are often inadequate. Commonly, different interventions are proposed for solving these issues separately. However, reasonable drawbacks arise when the structural retrofitting requires a direct contact with the target-member while the insulation layer is potentially interposed in between. In this scenario, the present research proposes a novel and unique system able to guarantee bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…At this scope, clay brick masonry panels were constructed and reinforced; thus, thermal conductivity test and diagonal compressive test were carried out. The goal was to compare the performances of a FRCM (lime-based matrix) with respect to the FRGM from Reference [25] by considering same reinforcing fabric (glass mesh) and identical geometrical dimensions (i.e., thickness of the plaster, brick, mortar joints, and masonry texture).…”
Section: Background Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…At this scope, clay brick masonry panels were constructed and reinforced; thus, thermal conductivity test and diagonal compressive test were carried out. The goal was to compare the performances of a FRCM (lime-based matrix) with respect to the FRGM from Reference [25] by considering same reinforcing fabric (glass mesh) and identical geometrical dimensions (i.e., thickness of the plaster, brick, mortar joints, and masonry texture).…”
Section: Background Summarymentioning
confidence: 99%
“…The result was a geopolymer-based mortar with valuable mechanical and thermal properties. Furthermore, a new inorganic-based composite was also developed by combining a glass fabric with the innovative mortar, making a Fabric Reinforced Geopolymer Mortar (FRGM), as reported in Reference [25]. The FRGM was found to have comparable tensile strength and global tensile stress-strain behavior with respect a traditional FRCM when the same fabric was considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite materials are well used in several engineering applications, ranging from marine to civil [1][2][3][4]. The fibre reinforced polymer (FRP) system is among the most widely used composite material in civil engineering applications due to its high mechanical performance, improved durability, and lightness [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that alkali activated materials, particularly alkali activated slag, could be produced with a comparable performance to that of the conventional concrete [ 7 ]. Studies have also revealed that alkali activated materials could be used as repair materials [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%